Interaction Studies Between Cyclic Peptide ADT-C3 (Ac-CADTPC-NH2) with E-Cadherin Protein using the Molecular Docking Method Simulated on 120ns - Parsaoran Siahaan; Vivitri Dewi Prasasty; Atiatul Manna; Dwi Hudiyanti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
The treatment of diseases that attack the brain is very difficult, because the delivery of drug molecules to the brain is often hindered by the blood-brain barrier (BBB). So that the drug delivery is not right on the target cell. Thus, was developed a method in modulation of intercellular junctions using ADTC3 cadherin peptide, Where the cadherin peptide is derived from the cadherin sequence itself. The method used in this research is molecular dynamics (DM) and molecular docking. In this study have been evaluated some peptide conformation in modulating intercellular junction. The results show that cyclic peptide ADT-C3 (Ac-CADTPC-NH2) was conducted DM for 120 ns (120000 ps), which has considerable activity in modulating intercellular junctions with binding energies of -33.10 kJ.mol-1 and Ki of 1.58 μM at the 79187 ps conformation. The binding site on residues Asp1, Trp2, Ile4, Lys25, Ser26, Asn27, Met92 in the adhesion arm-acceptor pocket region.